Green Bonds as a Green Investment to Prevent Greenwashing and Green Financial Crime in Indonesia - Serfiyani, Cita Yustisia (Indonesia Law Review, 2025)
Overcoming the climate crisis should not only be pursued from the aspect of technological invention but also from the financial aspect through issuing securities instruments that align with the green economy mission. Unfortunately, irresponsible parties such as corporations still use the green economy concept for personal gain through greenwashing and green financial crime. The presence of green bonds as green instruments shows a positive trend towards improving the quality of environmentally friendly technological innovations, building green infrastructure, and increasing income in line with increasing public participation in climate issues. However, its application in Indonesia is constrained by the complexity of issuance eligibility requirements which are detrimental to issuers and has not been accompanied by strict and transparent audit quality so that the public is disadvantaged when a default occurs so that legal protection for green bonds needs to be applied in several aspects. Therefore, the Indonesian public's interest in green bonds should be accompanied by an increase in the eligibility requirements and procedures for issuing green bonds.